Barriers and opportunities to bridge between hospital and community via rehabilitation exercises for people with disabilities: multi-ministerial R&D efforts in South Korea - Hogene Kim; Aerim Kim; Hye Min Choi; Jungah Lee; Jung Hwan Kim; Hyosun Kweon (Frontiers in Rehabilitation Sciences)
People with disabilities often experience limited participation in community-based exercise activities aimed at promoting health. The concept that “Exercise is Medicine” is widely acknowledged across societies and historical periods. However, there is a notable discontinuity between hospital-based and community-based health promotion efforts for people with disabilities. This article discusses multi-ministerial research and development (R&D) efforts in South Korea to address this issue, emphasizing the need for transitional strategies to successfully bridge the service gap. As the first collaborative multi-ministerial R&D initiative between the sports and clinical ministries in South Korea, this project focuses on community-based rehabilitation exercises through three major components: (1) Smart Exercise Equipment, (2) Disability-based Exercise Programs and Services, and (3) Data Continuity on Health Information. A standardized community rehabilitation exercise dataset was also developed to evaluate activities of daily living, primarily categorized into physiological outcomes during exercises, clinical assessments, and lifelog data measurements. The National Rehabilitation Center, under the Ministry of Health & Welfare and serving as the leading ministry, is dedicated to developing a rehabilitation exercise Living Lab that integrates these three components in collaboration with other ministries. This initiative aims to benefit people with disabilities by enhancing their health through data-driven rehabilitation exercise services. Furthermore, clinicians and community rehabilitation exercise providers could improve services by utilizing this standardized dataset, facilitating comparisons of clinical records through a public service platform.